Analisis Kandungan Merkuri (Hg) Pada Krim Pemutih Wajah Tidak Terdaftar Yang Beredar Di Pasar Inpres Kota Palu: Analysis of The Content of Mercury (Hg) In Unregistered Facial Whitening Creams Circulating In The Inpres Market Palu - Upik Rohaya; Nurlina Ibrahim; Jamaluddin Jamaluddin (Jurnal Farmasi Galenika (Galenika Journal of Pharmacy) (e-Journal), 2017)
Whitening cream is a mixture of chemicals and other materials to eliminate the the black spots on the skin. The purpose of this research was to determine whether unregistered facial whitening creams that contain mercury (Hg) and to determine the amount of mercury (Hg) levels of the facial whitening creams have circulated in the Inpres Market Palu. There are 10 samples were examined of facial whitening cream by using Purposive Sampling method. The testing of mercury content is divided into two stages first stage is qualitative testing (color test) and the second stage is quantitative testing atomic absorption Spectrophotometry using additional tools MVU (Mercury Vaporizer Unit). The result of the research show that all of 10 the samples contained mercury (Hg) with an average content of each sample A = 67,27 µg/g , B = 5349,47 µg/g, C = 137,49 µg/g, D = 159,25 µg/g, E = 90,22 µg/g, F = 33,61 µg/g, G = 31,87 µg/g, H = 32,36 µg/g, I = 3,63 µg/g and J = 3,52 µg/g.